Interplay between fibrinolysis and complement: plasmin cleavage of iC3b modulates immune responses. (4th February 2015) - Foley, J. H.; Peterson, E. A.; Lei, V.; Wan, L. W.; Krisinger, M. J.; Conway, E. M.
Summary Background The plasmin(ogen) and complement systems are simultaneously activated at sites of tissue injury, participating in hemostasis, wound healing, inflammation and immune surveillance. In particular, the C3 proteolytic fragment, iC3b, and its degradation product C3dg, which is generated by cleavage by factor I (FI) and the cofactor complement receptor CR1, are important in bridging innate and adaptive immunity. Via a thioester (TE) bond, iC3b and C3dg covalently tag pathogens, modulating phagocytosis and adaptive immune responses. Objective To examine plasmin‐mediated proteolysis of iC3b, and to evaluate the functional consequences, comparing the effects with products generated by FI/CR1 cleavage of iC3b. Methods Dose‐dependent and time‐dependent plasmin‐mediated cleavage of iC3b were characterized by analytical gel electrophoresis. The properties of the resultant TE bond‐containing fragments on phagocytosis and induction of pro‐inflammatory cytokines were measured in cell culture systems. Results At low concentrations, plasmin effectively cleaves iC3b, but at numerous previously undescribed sites, giving rise to novel C3c‐like and C3dg‐like moieties, the latter of which retain the TE bond. When attached to zymosan or erythrocytes and exposed to THP‐1 macrophages, the C3dg‐like proteins behave almost identically to the bona fide C3dg, yielding less phagocytosis as compared with the opsonin iC3b, and more macrophage secretion of the pro‐inflammatory cytokine, IL‐12. Conclusion Plasmin cleavage of iC3b provides a complement regulatory pathway that is as efficient as FI/CR1 but does not require a cellular cofactor.